Do Job Resources Reduce Turnover Intention through Employee Engagement among Generation Z - Maria Saniya Firdaus; Marliana Junaedi; Dominicus Wahyu Pradana (Journal of Applied Management and Business, 2026)
Aims - This study aims to examine the effect of job resources on turnover intention and to investigate the mediating role of employee engagement among Generation Z employees in the retail and service sectors. Methodology - Using a quantitative approach, data were collected from 158 Generation Z employees in Surabaya through an online questionnaire and analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings - The findings reveal that job resources have a significant positive effect on employee engagement but do not directly affect turnover intention. Employee engagement significantly reduces turnover intention and serves as a significant mediator in the relationship between job resources and turnover intention. These results indicate that job resources contribute to employee retention primarily by enchancing enhancing employee engagement rather than through a direct mechanism. Research Limitations - The study is limited to Generation Z employees in the retail and service sectors, which may restrict the generalisability of the findings to other industries and generations. Practically, organizations should focus on strengthening job autonomy, supervisory support, and performance feedback to foster employee engagement and reduce turnover intention. Originality - This study contributes to the Job Demands-Resources (JD-R) literature by providing empirical evidence of the mediating role of employee engagement in explaining employee retention among Generation Z workers in the retail and service context.